Penggunaan Large Language Models (LLM) Dalam Penulisan Artikel Berita: Sebuah Analisis Deskriptif Berbasis Literature Review - Rahman, Fahmi; Choirunnisa, Zuyyinna; Setyawan Putra, Yudistira Ardi Nugraha (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
The phenomenon of using Large Language Models (LLMs) in news production has raised significant debates concerning authenticity, journalistic ethics, and the quality of information delivered to the public. This study aims to analyze the phenomenon through a qualitative descriptive approach based on a literature review of academic works, media reports, regulations, and journalistic codes of ethics. The findings reveal that the adoption of LLMs in journalism offers efficiency in news production but simultaneously poses risks of factual inaccuracies, algorithmic bias, and reputational harm to media organizations. A comparative analysis of international and national regulations highlights the importance of transparency, human oversight, accountability, and bias mitigation in the use of this technology. The study underscores that the utilization of LLMs must be grounded in clear regulatory frameworks and strengthened digital literacy among both journalists and the public to ensure responsible implementation.